The Capability Approach and Archaeological Interpretation of Transformations: On the Role of Philosophy for Archaeology - Arponen V. P. J.; Ohlrau René; Kerig Tim (Open Archaeology)
Over its history, archaeology has seen a varied set of uses made of philosophy and philosophical concepts. A persistent critique has been that too often philosophical or more generally theoretical debates have made little difference in terms of empirical archaeological work and interpretation. In this article, we present results from an interdisciplinary study on the operationalisation of the Capability Approach in archaeology. We trace some of its implications as regards the understanding of identity and social organisation in archaeology and represent a model by way of which the Capability Approach can be operationalised in archaeology with the Cucuteni-Trypillia societies from 5050 to 2950 BCE as our case study. An analytic scheme is developed that relates archaeological categories to those of the United Nation’s Human Development Index.